Postoperative Recurrence of Instability Due to New Anterior Glenoid Rim Fractures After Arthroscopic Bankart Repair. (October 2017) - Nakagawa, Shigeto; Hirose, Takehito; Tachibana, Yuta; Iuchi, Ryo; Mae, Tatsuo
Background: Computed tomography (CT) sometimes reveals a new fracture of the anterior glenoid rim in patients with postoperative recurrence of instability after arthroscopic Bankart repair using suture anchors, but there have been few previous reports about such fractures. Hypothesis: The placement of a large number of suture anchors during arthroscopic Bankart repair might be associated with a new glenoid rim fracture. Study Design: Cohort study; Level of evidence, 3. Methods: Screw-in metal suture anchors were used until June 2011 and suture-based soft anchors from July 2011. A follow-up of at least 2 years was conducted for 128 shoulders treated using metal anchors (metal anchor group) and 129 shoulders treated using soft anchors (soft anchor group). The frequency and features of new glenoid rim fractures were investigated, and the influence of the number of suture anchors and other factors on fractures was also assessed. Results: There were 19 shoulders (14.8%) with postoperative recurrence in the metal anchor group and 23 shoulders (17.8%) in the soft anchor group. Among 37 shoulders evaluated by CT at recurrence, a new glenoid rim fracture was detected in 13 shoulders (35.1%; 5 shoulders in the metal anchor group and 8 shoulders in the soft anchor group). A fracture at the anchor insertion site was recognized in 4 shoulders from the metal anchor group and 6 shoulders from the soft anchor group, although linear fractures connecting several anchor holes were only seen in the soft anchor group. While new glenoid fractures occurred regardless of the number of suture anchors used, new fractures were significantly more frequent in teenagers at surgery and in junior high school or high school athletes. Such fractures did not only occur in contact athletes but were also found in overhead athletes. Conclusion: Postoperative recurrence of instability associated with a new glenoid rim fracture along the suture anchor insertion site was frequent after arthroscopic Bankart repair. These fractures might be related to placing multiple soft suture anchors in a linear arrangement.